MOLECULAR IDENTIFICATION OF SARCOPTES SCABIEI VAR. CUNICULI FROM SURABAYA AND MALANG REGIONS OF EAST JAVA - Desiandura, Kurnia; Lastuti, Nunuk Dyah Retno; Suwanti, Lucia Tri; Handijatno, Didik (Indonesian Journal of Tropical and Infectious Disease, 2017)
Scabies is a zoonotic skin disease caused by Sarcoptes scabiei mites. As an emerging/re-emerging parasitic disease, scabies represents a significant global threat to both human and animal health. Numerous cases of scabies in Indonesia have been reported, which support research on the prevalence of S. scabiei. However, most such studies have involved conventional morphological studies, with limited molecular diagnostic studies. The purpose of the present study was the genetic characterization of S. scabiei var. cuniculi in domestic rabbits to generate baseline genotypic data. S. scabiei var. cuniculi was isolated and identified from scabies-infected rabbits from the Surabaya and Malang regions of East Java. Molecular identification was performed using Polymerase Chain Reaction (PCR) using specific primers targeting the COX1 gene. We performed COX1 PCR using rabbit isolates of S. scabiei from Indonesia. To the best of our knowledge, no such study had been reported previously. This study was performed in the Laboratory of Veterinary Parasitology, Faculty of Veterinary Medicine and the Tropical Disease Diagnostic Center Laboratory, Universitas Airlangga. The results with agarose gel electrophoresis revealed a 289 bp PCR product amplified from the DNA of S. scabiei isolates from both Surabaya and Malang in accordance with the expected COX1 amplicon size, that indicated a single band 289 bp in length, demonstrating specific detection of S. scabiei var. cuniculi from Surabaya and Malang using COX1 primers. The results were consistent with the calculated amplicon size based on primer positions within the COX1 locus, with the forward primer spanning nucleotides 61–94, and the reverse primer spanning nucleotides 331–350 ( 350 âˆ’ 61 = 289 bp).  PCR genotyping of the isolates yielded an identical nucleotide length of 289 bp. Further studies are required to sequence the amplified fragments for homology assessment.